MENCIPTAKAN LINGKUNGAN RELIGIOUS PADA LEMBAGA PENDIDIKAN ISLAM - Budi Harto (Ta'dib, 2011)
he aims of this study were: 1) to figure out the way of creating religious atmosphere among teachers, 2) to figure out the way of creating religious atmosphere in terms of instructional materials, 3) to figure out the way of creating religious atmosphere in school environment where the educational process took place. To make sure that the students have Islamic characters (akhlaq) in primary education level by merely giving them understanding toward Islam were not effective. Conversely, familiarizing and modeling from teachers, parents, and Islamic environment gave better influence toward students’ religious characters formation.Kata kunci: pendidik, materi pelajaran integral, lingkungan sekolah